Throwing performance after resistance training and detraining. - Terzis, Gerasimos; Stratakos, Grigoris; Manta, Panagiota; Georgiadis, Giorgos (J Strength Cond Res, 2008)
The purpose of the present study was to investigate the effect of short-term resistance training and detraining on shot put throwing performance. Eleven young healthy subjects with basic shot put skills participated in 14 weeks of resistance training, which was followed by 4 weeks of detraining. Shot put performance in four field tests was measured before (T1) and after (T2) resistance training and after detraining (T3). At the same time points, one repetition maximum (1RM) was measured in squat, bench press, and leg press. Fat-free mass (FFM) was determined with dual x-ray absorptiometry and muscle biopsies obtained from vastus lateralis for the determination of fiber type composition and cross-sectional area (CSA). 1RM strength increased 22-34% (p < 0.01) at T2 and decreased 4-5% (not significantly different) at T3. Shot put performance increased 6-12% (p < 0.05) after training and remained unaltered after detraining. FFM increased at T2 (p < 0.05) but remained unchanged between T2 and T3. Muscle fiber CSA increased 12-18% (p < 0.05) at T2. Type I muscle fiber CSA was not altered after detraining, but type IIa and IIx fiber CSA was reduced 10-12% (p < 0.05). The percentage of type IIx muscle fibers was reduced after training (T1 = 18.7 +/- 4, T2 = 10.4 +/- 1; p < 0.05), and it was increased at T3 compared with T2 (T3 = 13.7 +/- 1; p < 0.05). These results suggest that shot put performance remains unaltered after 4 weeks of complete detraining in moderately resistance-trained subjects. This might be linked to the concomitant reduction of muscle fiber CSA and increase in the percentage of type IIx muscle fibers.
Keywords: Absorptiometry, Photon; Adult; Arm; Athletic Performance; Biopsy; Body Mass Index; Humans; Male; Movement; Muscle Fibers, Skeletal; Muscle, Skeletal; Physical Education and Training